PENGARUH SERTIFIKASI TERHADAP KINERJA GURU DENGAN SUPERVISI AKADEMIK DAN INTERNAL LOCUS OF CONTROL SEBAGAI VARIABEL MODERASI - Triman - -; Suprayitno - - (Universitas Slamet Riyadi, 2013)
ABSTRACT This research aims to analyses: (1) effect certification, academic supervision, internal locus of control to teacher performance; (2) role of academic supervision as moderator effect certification to teacher performance; (3) role of internal locus of control as moderator effect certification to teacher performance. Populations on this research are all of teacher’s certificated in all Public Elementary School on Bendosari Disctrict Sukoharjo Regency consist of 161 teachers. The samples of this research consist of 80 respondents taken by proportional cluster random sampling technique. Data collecting with questionnaire technique through validity and reliability test. The data analyze use the multiple regression analysis and moderated regression analysis through standardized residual method, and previously the researcher uses classical assumption test. The result reveals that (1) there is a significance effect between certification to teacher performance; (2) there is a significance effect between academic supervision to teacher performance; (3) there is a significance effect between internal locus of control to teacher performance; (4) academic supervision moderates the effect of certification to teacher performance; (5) internal locus of control moderates the effect of certification to teacher performance. Keywords: certification, academic supervision, internal locus of control, teacher performance